BIFURCATION ANALYSIS OF FRACTIONAL ORDER RÖSSLER SYSTEM - Markoski, Gjorgji (Matematichki Bilten, 2018)
In the paper Fractional Multistep differential transform method it is used for investigation of the the approximate numerical solutions of the fractional-order Rössler chaotic system. Numerical results are presented graphically, with bifurcation diagrams and Lyapunov exponents, for different values of the parameters.